A water reducing agent for active powder concrete and its application

The water reducing agent prepared by the open ring metathesis polymerization method solves the problem that the traditional water reducing agent is not ideal when using fly ash and silica fume, and achieves efficient water reduction and sustained release effects on active powders and cement. Improves the flowability and ease of concrete.

CN118955875BActive Publication Date: 2025-02-25THE FIRST ENGINEERING COMPANY OF CCCC FOURTH HARBOUR ENGINEERING CO LTD +2
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411015497.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-26
Publication Date
2025-02-25
Estimated Expiration
2044-07-26

AI Technical Summary

Technical Problem

Traditional polycarboxylic acid water reducing agents are not effective when using fly ash and silica fume, resulting in poor compatibility between fly ash and silica fume and cement. A large amount of water reducing agent is required to achieve the expected effect, but too many water reducing agents are used. Joining will affect early intensity.

Method used

The water reducer prepared by ring-opening metathesis polymerization method is prepared by copolymerization of polyether and silane monomer, forming side chains such as alternating carboxylate and high molecular weight polyether, carboxylate and polysilica hydroxyl group. Alternating comb copolymers.

Benefits of technology

This water reducer has an extremely high water reduction rate on both active powder and cement, which improves the performance of concrete and has a sustained release effect, improves the flowability and ease of concrete, and reduces the impact on early strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118955875B_ABST
    Figure CN118955875B_ABST
Patent Text Reader

Abstract

The present invention discloses a water reducer for active powder concrete and its application, belonging to the technical field of building concrete admixtures. The present invention synthesizes a water reducer for active powder concrete by synthesizing polyether monomers, synthesizing silane monomers, controlling polymerization reaction and hydrolysis reaction, and its side chain is a comb-shaped copolymer in which carboxylates and high molecular weight polyethers are alternating, and carboxylates and polysilicon hydroxyls are alternating. The water reducer of the present invention has the characteristics of controllable chemical structure, high polymerization efficiency and simple process. The alternating polysilicon hydroxyls and carboxylates can act on cement and active powders such as fly ash, silica ash, slag powder, etc. at the same time, and the carboxylates and high molecular weight polyethers can effectively improve the compatibility and dispersibility between the components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of concrete admixtures, and in particular to a water reducing agent for active powder concrete and application thereof. Background Art

[0002] In the traditional sense, polycarboxylic acid water-reducing agent is a polymer formed by the free radical polymerization reaction of unsaturated monomers containing carboxyl groups and unsaturated monomers containing other functional groups. It is a random copolymer with a comb-shaped molecular structure. It has the characteristics of high water reduction rate, small change of slump over time, and good adaptability to different types of cement.

[0003] With the rapid development of the construction industry, the development of low-cost and environmentally friendly concrete has become the mainstream. Using fly ash, blast furnace slag powder and silica fume obtained from industrial waste to replace part of cement is a common means of reducing costs and improving concrete performance. The polymerization ability of traditional free radical polymerization is weak, and the molecular weight of the polyether introduced in the comb-like molecular structure is often small, resulting in the water reducer effect not reaching the desired level. The polycarboxylic acid water reducer currently sold on the market is not ideal for fly ash and silica fume. Its molecular structure design is mainly aimed at the surface activity of cement, and the surface structure of fly ash and silica fume is quite different from that of cement, so it cannot achieve a good adsorption and anchoring effect, which leads to poor compatibility between fly ash, silica fume and cement. A large amount of water reducer needs to be added to achieve the desired effect, but the addition of too much water reducer is bound to affect its early strength. Summary of the invention

[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides a water reducing agent for active powder concrete, which has an ultra-high water reducing rate for various active powders and cements, effectively improves the performance of concrete, and has a slow-release effect.

[0005] The object of the present invention is to provide a water reducing agent for active powder concrete, which is achieved by the following scheme:

[0006] A water reducing agent for active powder concrete, the water reducing agent is prepared by the following steps:

[0007] The specific preparation method is as follows:

[0008] S1. Synthesis of polyether monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add an amine catalyst, add polyether to the reactor at room temperature, heat to 100-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain a polyether monomer;

[0009] S2. Synthesis of silane monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add an amine catalyst, add silane to the reactor at room temperature, heat to 100-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain the silane monomer;

[0010] S3. Polymerization reaction: Under a nitrogen atmosphere, add the obtained polyether monomer A and silane monomer B into a reactor and dissolve them. Add a catalyst and dissolve it in a solvent. Slowly add it dropwise to the reactor to carry out ring-opening metathesis polymerization. Heat to 50-100°C and react for 1-5 hours. Add vinyl ethyl ether to quench the reaction. Remove the solvent and obtain a polymerization product by recrystallization through acetone.

[0011] S4. Hydrolysis reaction: The polymer product is added to a mixed solution of sodium hydroxide aqueous solution and alcohol and stirred. The pH of the solution is adjusted to 6-7 by saturated ammonium chloride aqueous solution, and then extracted three times with dichloromethane. The organic phase is collected and evaporated to obtain the water reducing agent.

[0012] The invention provides a water reducer, which is prepared by a ring-opening metathesis polymerization method. The method has a simple process, controllable molecular weight, and particularly strong polymerization ability, and can effectively prepare a high molecular weight polyether into a comb-like polymer. The alkaline and easy ring-opening property of the imide structure is utilized to obtain a comb-like polymer with alternating carboxyl and silanol side chains.

[0013] Among them, it should be noted that:

[0014] In the extraction and washing steps involved in the present invention, the volume ratio of the extraction solvent to the extracted liquid, and the volume ratio of the washing solvent to the washed liquid are both 1:5.

[0015] The concentration of the sodium hydroxide aqueous solution used in steps S1 and S2 is 1 to 2 mol / L.

[0016] Preferably, the silica fume is semi-densified silica fume with a SiO2 content of 96%; and the slag powder is S95 grade granulated blast furnace slag powder.

[0017] The polyether in the present invention is mainly used as one of the side chains of the comb-like polymer to produce a steric hindrance effect, effectively increasing the water reduction of the synthesized polymer. Preferably, the polyether is aminopolyethylene glycol monomethyl ether, and the average molecular weight of the aminopolyethylene glycol monomethyl ether is 400 to 10,000, and more preferably 2,000 to 5,000.

[0018] The silane in the present invention is mainly used as one of the side chains of the comb-like polymer, and can form a polysilicic hydroxy compound after hydrolysis, which plays a role in adsorbing substances with SiO2 as the main component in the active powder, such as fly ash and silica fume.

[0019] Preferably, the silane is at least one of N-aminoethyl-3-aminopropylmethyldimethoxysilane and 3-aminopropyltriethoxysilane.

[0020] More preferably, the silane used in the present invention is 3-aminopropyltriethoxysilane.

[0021] The nadic anhydride used in the present invention first provides an active double bond for ring-opening metathesis polymerization, and provides a negatively charged carboxyl group after ring opening through polymerization and hydrolysis. The carboxyl group after ring opening forms an alternating copolymerized comb-like polymer with a polysilicyl compound or a polyether to play the role of adsorption and water-reducing dispersion.

[0022] The amine catalyst used in the present invention is one or more of 4-dimethylaminopyridine, triethylamine and pyridine.

[0023] Preferably, the amine catalyst used in the present invention is at least one of triethylamine and pyridine.

[0024] The present invention adopts a ring-opening metathesis polymerization method, which can effectively prepare a large molecular weight, large steric hindrance polymer into a comb polymer. Preferably, the catalyst is one or more of Grubbs first-generation catalyst, Grubbs second-generation catalyst, and Grubbs third-generation catalyst.

[0025] Preferably, a Grubbs second generation catalyst is used as the catalyst for the ring-opening metathesis polymerization.

[0026] The synthesized monomers of the present invention have relatively large steric hindrance, and require a relatively high temperature for polymerization. A relatively high boiling point solvent is required for polymerization. Preferably, the solvent is selected from one or more of dichloromethane, chloroform, tetrahydrofuran and toluene.

[0027] Preferably, the solvent used in the polymerization is at least one of chloroform and toluene.

[0028] The present invention hydrolyzes imide into amide and carboxylate by alkaline hydrolysis, and hydrolyzes silane into polysilicone, and obtains partially hydrolyzed and completely hydrolyzed water reducers by different reaction conditions. The partially hydrolyzed water reducer has a certain sustained release effect, and the completely hydrolyzed water reducer has a more efficient water absorption rate. The hydrolysis conditions are that the concentration of the configured sodium hydroxide aqueous solution is 1-3 mol / L, the volume ratio of alcohol to the sodium hydroxide aqueous solution is (1:1)-(1:3), the alcohol is at least one of methanol and ethanol, the hydrolysis temperature of the hydrolysis reaction is 25-50°C, and the time is 10-60 minutes.

[0029] Preferably, the conditions for hydrolysis in the present invention are that the concentration of the aqueous sodium hydroxide solution is 1-2 mol / L, the alcohol is methanol, and the volume ratio of the alcohol to the aqueous sodium hydroxide solution is 1:1, the hydrolysis temperature is 25-40° C., and the time is 10-60 min.

[0030] The present invention modifies nadic anhydride by acylation with polyether or silane to obtain two different monomers, wherein the molar ratio of nadic anhydride, polyether and amine catalyst is (1-1.5):1:(1.5-3), and the molar ratio of nadic anhydride, silane and amine catalyst is: (1-1.5):1:(1.5-3).

[0031] The invention copolymerizes two different monomers through ring-opening metathesis polymerization to obtain a comb-shaped polymer with side chains of polyether, polysilicyl and carboxylate. During the copolymerization, the molar ratio of different monomers to catalyst is (0.5-4): (10-20): (0.5-1).

[0032] The present invention also protects a reactive powder concrete, which comprises the following components in terms of mix ratio:

[0033] Fly ash: 50~250kg / m 3 ;

[0034] Silica fume: 50~250kg / m 3 ;

[0035] Slag powder: 50~250kg / m 3 ;

[0036] Cement: 200-400kg / m 3 ;

[0037] Sand: 700~850kg / m 3 ;

[0038] Crushed stone: 850~950kg / m 3 ;

[0039] Water: 150~200kg / m 3 ;

[0040] Water reducing agent: 3~10kg / m 3

[0041] Wherein, the water reducing agent is the water reducing agent prepared by the above method.

[0042] The present invention provides a water reducing agent for active powder concrete, wherein a comb-shaped copolymer having alternating side chains of carboxylate and high molecular weight polyether, and alternating side chains of carboxylate and polysilicyl is synthesized by ring-opening metathesis polymerization of two monomers. The water reducing agent has a good water reducing rate for active powders with silicate structure and silicon dioxide structure, can be used for active powder concrete, and has the following beneficial effects:

[0043] (1) The polysilicic acid hydroxyl structure of the side chain of the water reducer can make it adsorb on active powders with SiO2 as the main component, such as fly ash and silica ash, and some of the silicic acid hydroxyl groups form covalent bonds with the hydroxyl groups on such active powders under the condition of exothermic mixing of cement, thus playing an anchoring role; the high molecular weight polyether and carboxylate structure of the side chain introduced by ring-opening metathesis polymerization can effectively block the interaction between active powders and cement particles, reduce the agglomeration of particles, and at the same time, the carboxylate structure has an electrostatic attraction effect with the positive charge on the surface of silicate structures such as cement and slag powder, thus playing an anchoring role;

[0044] (2) The alternating structure of polysilicone and carboxylate enables the polymer to effectively adsorb active powder and cement. The alternating structure of polyether and carboxylate can coordinate through electrostatic repulsion effect, steric hindrance effect and hydration film lubrication effect, greatly improving the lubrication between cement particles, between active powders, and between cement particles and active powder particles, greatly enhancing the fluidity and workability of concrete.

[0045] (3) Compared with the ester structure, the imide structure is easier to open under alkaline conditions to obtain amide and carboxylate, and is more easily hydrolyzed during the concrete processing process. In addition, the ratio of imide ring opening to silane hydrolysis in the polymer can be controlled by a simple hydrolysis reaction to obtain a water-reducing agent with a slow-release effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The polymerization process of the water reducing agent of the present invention;

[0047] Figure 2 This is the NMR spectrum of the polyether monomer A1 prepared in the present invention. DETAILED DESCRIPTION

[0048] The following is a more detailed description of the specific implementation method of the present invention, the purpose of which is to explain the concept and characteristics of the present invention, and it cannot be used to limit the scope of protection of the present invention. Any equivalent changes or modifications made according to the spirit of the present invention should be included in the scope of protection of the present invention.

[0049] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0050] Polyether 1: aminopolyethylene glycol monomethyl ether, average molecular weight of 2000, homemade, preparation method is as follows: under nitrogen atmosphere, add 1 mole of polyethylene glycol monomethyl ether with average molecular weight of 2000 (Annaiji Chemical, product number P2186), 3 moles of p-toluenesulfonyl chloride (Annaiji Chemical, product number T35955), 3 moles of triethylamine to the reactor, use dichloromethane as solvent, stir at 50 ° C for 10 hours, and wait for the reaction to end. First wash three times with 1 mol / L hydrochloric acid solution, then wash three times with 1 mol / L sodium hydroxide aqueous solution, collect the organic phase and evaporate.

[0051] The obtained solid was dissolved in ammonia water, stirred at room temperature for three days, and then a 2 mol / L sodium hydroxide aqueous solution was added and stirred for 2 hours. The mixture was extracted with dichloromethane three times, and the organic phase was collected, evaporated, and recrystallized with ether to obtain aminoethylene glycol monomethyl ether with an average molecular weight of 2000.

[0052] Polyether 2: amino polyethylene glycol monomethyl ether, average molecular weight 5000, homemade, the preparation method is different from that of polyether 1, except that the polyethylene glycol monomethyl ether used is Shanghai McLean, product number M813520;

[0053] Polyether 3: aminopolyethylene glycol monomethyl ether, average molecular weight of 550, homemade, preparation method is as follows: under nitrogen atmosphere, add 1 mol part of polyethylene glycol monomethyl ether with average molecular weight of 550 (Shanghai McLean, product number M834670), 3 mol parts of p-toluenesulfonyl chloride, 3 mol parts of triethylamine into the reactor, use dichloromethane as solvent, stir at 50 ℃ for 10 hours, after the reaction is completed, remove the solvent, dissolve in ethyl acetate solution, wash three times with 1 mol / L hydrochloric acid solution, collect the aqueous phase, adjust the pH of the aqueous phase to 8-10 with 2 mol / L sodium hydroxide aqueous solution, extract with dichloromethane, collect the organic phase, and evaporate.

[0054] The obtained solid was dissolved in ammonia water, stirred at room temperature for one day, and then a 2 mol / L sodium hydroxide aqueous solution was added and stirred for 2 hours. The mixture was extracted three times with dichloromethane, and the organic phase was collected and evaporated to obtain aminoethylene glycol monomethyl ether with an average molecular weight of 550.

[0055] Polyether 4: amino polyethylene glycol monomethyl ether, average molecular weight of 10,000, homemade, the preparation method is different from that of polyether 1, except that the polyethylene glycol monomethyl ether used is Shanghai McLean, product number 76291 polyethylene glycol monomethyl ether.

[0056] Nadic anhydride: Shanghai MacLean, product number N814504;

[0057] Silane: 3-aminopropyltriethoxysilane: Shanghai MacLean, product number A800523;

[0058] Grubbs second-generation catalyst: Anaiji Chemical, product number G789000;

[0059] Cement: Portland cement, PII 52.5R, produced by Zhujiang Cement Plant;

[0060] Silica fume: semi-densified silica fume, SiO2 content 96%, purchased from Sichuan Ewende, 960U;

[0061] Fly ash: Class II fly ash, Wuhan Lianhekang Biotechnology Co., Ltd.;

[0062] Sand: Qingyuan river sand, fineness modulus 2.0-3.0;

[0063] Crushed stone: Guangxi diabase, particle size 5-8mm;

[0064] S95 grade blast furnace slag powder: Shijiazhuang Tonglei Mining Products;

[0065] Commercially available water reducer 1: standard polycarboxylate water reducer, Guangdong Wengjiang Chemical Reagent, PA96208;

[0066] Commercially available water reducer 2: sustained-release polycarboxylate water reducer, Liaoning Kelong Fine Chemicals, SPS-200;

[0067] The following is the test method of the performance parameters involved in the present invention:

[0068] (1) Relative molecular weight: gel permeation chromatography-differential detector (Waters, USA);

[0069] (2) Molecular weight distribution: gel permeation chromatography-differential detector (Waters, USA);

[0070] (3) Water reduction rate: The water reduction rate of cement mortar is measured according to GB / T 8077-2012;

[0071] (4) Degree of hydrolysis γ: Calculation of the ratio of NMR characteristic peaks. Weigh 10-20 mg of the polymer before and after hydrolysis, add it to a special NMR tube, and add 0.5-0.6 ml of deuterated chloroform solution to dissolve it. Use a 400 MHz NMR spectrometer (Bruker, Germany) to test it, and obtain the NMR spectra of different products and analyze them. First, analyze the spectrum of the amide part. There is a characteristic peak δ3.25 before hydrolysis, which becomes δ2.83 after hydrolysis. Based on this, the degree of hydrolysis of the amide is calculated by integration. Before the hydrolysis of silane, there are characteristic peaks of δ1.21 and δ1.51. After complete hydrolysis, δ'1.21 does not change, and δ'1.51 disappears. Based on this, the degree of hydrolysis of silane can be calculated by integration. Degree of hydrolysis

[0072] (5) Collapse: measured by the method described in GB / 8076-2008;

[0073] (6) Expansion: measured by the method described in GB / 8076-2008.

[0074] The polyether monomer A in the present invention is prepared by the following method:

[0075] Polyether Monomer A1

[0076] Under nitrogen atmosphere, 1.5 mol of nadic anhydride was added to the reactor and dissolved in toluene. After adding 2 mol of triethylamine, 1 mol of polyether 1 was added to the reactor at room temperature. The temperature was raised to 110°C and the reaction was carried out for 10 hours, and then the reaction was stopped. After the solution was cooled, the toluene was evaporated and the obtained product was dissolved in dichloromethane and washed three times with 1 mol / L sodium hydroxide aqueous solution. The organic phase was collected and evaporated to obtain polyether monomer A1.

[0077] Polyether Monomer A2

[0078] Compared with the polyether monomer A1, the difference is that the polyether used is polyether 2;

[0079] Polyether Monomer A3

[0080] Compared with the polyether monomer A1, the difference is that the polyether used is polyether 3;

[0081] Polyether Monomer A4

[0082] Compared with the polyether monomer A1, the difference is that the polyether used is polyether 4;

[0083] The silane monomer B in the present invention is prepared by the following method:

[0084] Under nitrogen atmosphere, 1.2 mol of nadic anhydride was added to the reactor and dissolved in toluene. After adding 2.0 mol of triethylamine, 1 mol of 3-aminopropyltriethoxysilane was added to the reactor at room temperature. The temperature was raised to 110°C and the reaction was stopped after 8 hours of reaction. After the solution was cooled, the toluene was evaporated and the obtained product was dissolved in dichloromethane and washed three times with 1 mol / L sodium hydroxide aqueous solution. The organic phase was collected and evaporated to obtain silane monomer B.

[0085] The water reducing agent of the present invention is prepared by the following steps, and its relative molecular weight, molecular weight distribution, hydrolysis degree and mortar water reduction rate are measured as shown in Table 1:

[0086] Water reducing agent A-1

[0087] Polymerization reaction: Under a nitrogen atmosphere, add 1 mol of the obtained polyether monomer A1 and 10 mol of silane monomer B to a reactor and dissolve them in toluene, add 0.5 mol of Grubbs second-generation catalyst and dissolve it in a solvent, slowly add it dropwise to the reactor, and carry out ring-opening metathesis polymerization. The reaction temperature is 80°C. After reacting for 2 hours, vinyl ethyl ether is added to quench the reaction, the solvent is evaporated, and the polymerization product is obtained by recrystallization.

[0088] Hydrolysis reaction: prepare 2 mol / L sodium hydroxide aqueous solution, add an equal volume of methanol, add the obtained polymer product thereto and stir for 50 min at a hydrolysis temperature of 40°C, adjust the solution pH to 6-7 with a saturated ammonium chloride aqueous solution, extract with dichloromethane three times, collect the organic phase, and evaporate to obtain solid polycarboxylic acid water reducer A-1.

[0089] Water reducing agent A-2

[0090] Compared with the step of water reducing agent A-1, the difference is that polyether monomer A1 is replaced by polyether monomer A2, and the ring-opening metathesis polymerization reaction temperature is 100°C;

[0091] Water reducing agent A-3

[0092] Compared with the step of water reducing agent A-1, the difference is that polyether monomer A1 is replaced by polyether monomer A3, and the ring-opening metathesis polymerization reaction temperature is 60°C;

[0093] Water reducing agent A-4

[0094] Compared with the step of water reducing agent A-1, the difference is that polyether monomer A1 is replaced by polyether monomer A4, and the ring-opening metathesis polymerization reaction temperature is 110°C;

[0095] Water reducing agent A-5

[0096] Compared with the step of water reducing agent A-2, the difference is that the concentration of the sodium hydroxide aqueous solution used in the hydrolysis reaction is 1 mol / L, the hydrolysis temperature is 25°C, and the stirring is 10 min;

[0097] Water reducing agent A-6

[0098] Compared with the step of water reducing agent A-2, the difference is that the concentration of the sodium hydroxide aqueous solution used in the hydrolysis reaction is 1 mol / L, the hydrolysis temperature is 25°C, and the stirring is 20 minutes.

[0099] Table 1 Performance test of water reducing agent

[0100] Water reducing agent Relative molecular weight Molecular weight distribution Degree of hydrolysis Water reduction rate Water reducing agent A-1 72305 1.23 100% 37.43% Water reducing agent A-2 79510 1.29 100% 39.52% Water reducing agent A-3 94000 1.31 100% 35.15% Water reducing agent A-4 62610 1.15 100% 30.24% Water reducing agent A-5 77432 1.15 34% 33.49% Water reducing agent A-6 78610 1.21 54% 34.55% Commercially available water reducing agent 1 / / / 33.12% Commercially available water reducing agent 2 / / / 28.59%

[0101] Examples 1 to 8

[0102] A reactive powder concrete, the preparation method of which comprises the following steps: mixing fly ash, silica fume, slag powder, cement, sand and crushed stone according to the mix ratio, stirring for 3 minutes, adding water, stirring for 3 minutes, adding a water reducing agent, continuing to stir for 10 minutes and then discharging, wherein the formula of the reactive powder concrete is shown in Table 2, and the performance of the concrete is tested, and the results are shown in Table 4.

[0103] Table 2 Reactive powder concrete formula (Examples 1 to 8, in terms of mix ratio kg / m 3 )

[0104]

[0105]

[0106] Comparative Examples 1 to 4

[0107] The preparation method is consistent with that of Examples 1 to 8.

[0108] Table 3 Reactive powder concrete formula (Comparative Examples 1 to 4, in terms of mix ratio kg / m 3 )

[0109] Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 cement 420 300 420 300 Silica Fume 0 120 0 120 Fly ash 0 60 0 60 Slag powder 140 80 140 80 Sand 788 788 788 788 gravel 895 895 895 895 Commercially available water reducing agent 1 4.8 4.8 Commercially available water reducing agent 2 4.8 4.8 water 168 168 168 168

[0110] Table 4 Performance test of reactive powder concrete

[0111]

[0112]

[0113] The experimental results show that the water reducing agent prepared by the present invention has excellent properties. According to the data in Table 1, the water reducing rate of the prepared water reducing agent is as high as 39.50%, which is better than the standard water reducing agent on the market.

[0114] Comparing Comparative Example 1 with Comparative Example 2, when active powders such as silica fume and fly ash with SiO2 as the main component are added to concrete containing a commercially available water reducing agent, the fluidity of the concrete is affected to a certain extent, and the collapse and expansion are significantly reduced.

[0115] From the data of Examples 1 to 7 and Comparative Examples 1 to 2 in Table 3, it can be seen that the concrete with the standard water reducer lost fluidity after 2 hours. Comparative Examples 3 to 4 show that when the commercially available slow-release water reducer is added to the concrete with active powders such as silica fume and fly ash with SiO2 as the main component, the fluidity of the concrete will also be affected, and the initial collapse and expansion will be significantly reduced. From Examples 8 to 9, it can be seen that the water reducers A-5 and A-6 obtained by partial hydrolysis have obvious slow-release properties and have a significant relationship with the degree of hydrolysis. Among them, the concrete with the water reducer A-5 still has fluidity at 4 hours, the collapse loss is only 43mm, and the expansion can reach 470nm, which is better than the commercially available slow-release water reducer.

[0116] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A water reducing agent for reactive powder concrete, characterized in that: The water reducing agent is prepared by the following steps: S1. Synthesis of polyether monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add an amine catalyst, add polyether to the reactor at room temperature, heat to 100-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with a sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain a polyether monomer; S2. Synthesis of silane monomer: In a nitrogen atmosphere, add nadic anhydride to a reactor and dissolve it in toluene, add an amine catalyst, add silane to the reactor at room temperature, heat to 100-120°C and react for 8-16 hours, stop the reaction, evaporate to remove toluene, dissolve the obtained product in dichloromethane, wash three times with sodium hydroxide aqueous solution, collect the organic phase, and evaporate to obtain the silane monomer; S3. Polymerization reaction: In a nitrogen atmosphere, add the obtained polyether monomer A and silane monomer B to a reactor and dissolve them, add a catalyst and dissolve it in a solvent, slowly add it dropwise to the reactor, and perform ring-opening metathesis polymerization. After heating to 50-100° C. and reacting for 1-5 hours, add vinyl ethyl ether to quench the reaction, remove the solvent, and obtain a polymer product by recrystallization through acetone; S4. Hydrolysis reaction: The polymer product was added to a mixed solution of an aqueous sodium hydroxide solution and an alcohol and stirred, the pH of the solution was adjusted to 6 to 7 by a saturated aqueous ammonium chloride solution, extracted three times with dichloromethane, the organic phase was collected, and evaporated to obtain the water reducing agent; The polyether is aminopolyethylene glycol monomethyl ether, and the average molecular weight of the aminopolyethylene glycol monomethyl ether is 400 to 10000; the silane is at least one of N-aminoethyl-3-aminopropylmethyldimethoxysilane and 3-aminopropyltriethoxysilane; the hydrolysis conditions in step S4 are that the concentration of the configured sodium hydroxide aqueous solution is 1 to 3 mol / L, the volume ratio of alcohol to the sodium hydroxide aqueous solution is (1:1) to (1:3), the alcohol is at least one of methanol and ethanol, the hydrolysis temperature of the hydrolysis reaction is 25 to 50°C, and the time is 10 to 60 minutes.

2. A water reducing agent for reactive powder concrete according to claim 1, characterized in that: The amine-based catalyst includes one or more of 4-dimethylaminopyridine, triethylamine and pyridine.

3. A water reducing agent for reactive powder concrete according to claim 1, characterized in that: The catalyst is one or more of a Grubbs first generation catalyst, a Grubbs second generation catalyst, and a Grubbs third generation catalyst.

4. A water reducing agent for reactive powder concrete according to claim 1, characterized in that: The solvent in step S3 is one or more of dichloromethane, chloroform, tetrahydrofuran and toluene.

5. A water reducing agent for reactive powder concrete according to claim 1, characterized in that: The molar ratio of nadic anhydride, polyether and amine catalyst in step S1 is (1-1.5):1:(1.5-3); the molar ratio of nadic anhydride, silane and amine catalyst in step S2 is: (1-1.5):1:(1.5-3).

6. A water reducing agent for reactive powder concrete according to claim 1, characterized in that: In step S3, the molar ratio of polyether monomer A, silane monomer B, and catalyst is (0.5-4): (10-20): (0.5-1).

7. A reactive powder concrete, characterized in that: In terms of mix ratio, it includes the following components: Fly ash: 50~250kg / m 3 ; Silica fume: 50~250kg / m 3 ; Slag powder: 50~250kg / m 3 ; Cement: 300-400kg / m 3 ; Sand: 700~850kg / m 3 ; Crushed stone: 850~950kg / m 3 ; Water: 150~200kg / m 3 ; Water reducing agent: 3~10kg / m 3 , the water reducing agent is the water reducing agent according to any one of claims 1 to 6.

Citation Information

Patent Citations

  • Nano material as well as preparation method and application thereof

    CN113456827A

  • Synthesis method of sequence-controllable multi-block copolymer brush

    CN116640276A